Pengaruh Efektivitas Sistem Pengendalian Internal, Kesesuaian Kompensasi Dan Integritas Terhadap Kecenderungan Kecurangan (Fraud) Pada Koperasi Simpan Pinjam Di Kecamatan Denpasar Selatan - Ni Kadek Dwi Juliani; I Putu Deddy Samtika Putra (UNHI Press, 2023)
The purpose of this study was to determine the effect of the effectiveness of the internal control system, suitability of compensation and integrity on the tendency of fraud (fraud). The population in this study were 49 KSP and a sample of 22 KSP with a total of 88 respondents. The power analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that 1) the effectiveness of the internal control system has a negative and significant effect on fraud tendencies. 2) suitability of compensation has a negative and significant effect on the tendency of fraud (fraud). 3) integrity has a negative and significant effect on fraud tendencies.